2021
DOI: 10.5582/ddt.2021.01053
|View full text |Cite
|
Sign up to set email alerts
|

Association between anaphylaxis and anti-influenza drug use: An analysis of the Japanese Adverse Drug Event Report database

Abstract: Anti-influenza drug, anaphylaxis, Japanese Adverse Drug Event Report database, laninamivir, peramivir, baloxavirWe aimed to investigate the association between anaphylaxis and anti-influenza drug use using the Japanese Adverse Drug Event Report (JADER) database, a national spontaneous reporting database in Japan. We surveyed registered cases from the JADER database between April 2004 and November 2019. The target drugs were five anti-influenza drugs, namely oseltamivir, zanamivir, peramivir, laninamivir, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In this study, RORs and ICs were used for the signal detection of SREs as previously Flow diagram of the study. reported (14,15). RORs, ICs, and their 95% confidence intervals (CIs) were calculated using a two-by-two contingency table (Table 2) and equations as described below.…”
Section: Signal Detectionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, RORs and ICs were used for the signal detection of SREs as previously Flow diagram of the study. reported (14,15). RORs, ICs, and their 95% confidence intervals (CIs) were calculated using a two-by-two contingency table (Table 2) and equations as described below.…”
Section: Signal Detectionmentioning
confidence: 95%
“…However, as the World Health Organization, PMDA, and other regulatory authorities have suggested, it is possible to estimate the potential risk of adverse events associated with a target drug by calculating parameters such as reporting odds ratios (RORs) and information components (ICs) based on two-by-two contingency tables ( 12 ). In this study, RORs and ICs were used for the signal detection of SREs as previously reported ( 14 , 15 ). RORs, ICs, and their 95% confidence intervals (CIs) were calculated using a two-by-two contingency table ( Table 2 ) and equations as described below.…”
Section: Methodsmentioning
confidence: 99%
“…This study used ROR and IC to evaluate the signal detection of IOHs, as previously reported ( 9 , 10 ). The ROR is an AE signal index, the odds ratio of reporting a particular AE versus all other AEs associated with the target drugs, compared to the reporting odds for all other drugs.…”
Section: Methodsmentioning
confidence: 99%
“…The calculations were performed using Excel for Microsoft 365 (Microsoft Corporation, Redmond, WA, USA). The safety signals for OARs were positive when the lower limit of the 95% CI of the ROR exceeded 1, and that of the IC exceeded 0 (17). III shows the results of the disproportionality analysis with anticancer drugs which showed RORs with the lower limit of the 95% CI >1 and that of IC >0 for each of the OARs.…”
Section: Ic Equationsmentioning
confidence: 99%
“…The Japanese Adverse Drug Event Report (JADER) is a nationwide database of spontaneous reports of ADR published by the Pharmaceuticals and Medical Devices Agency (PMDA), a pharmaceutical regulatory authority in Japan. The calculation of reporting odds ratio (RORs) and information components (ICs) (15)(16)(17)(18) based on safety signal data from JADER allows for the investigation of anticancer drug-induced OARs.…”
mentioning
confidence: 99%